Advanced optical nanolithography by enhanced transmission through bull’s eye nanostructured meta-mask - Kim Taeyeon; Ahn Heesang; Kim Soojung; Song Hyerin; Choi Jong-ryul; Kim Kyujung (Nanophotonics)
Plasmonic optical nanolithography using extraordinary optical transmission through a metallic nanohole mask has been actively applied to the high-resolution fabrication of nanostructures over a large area. Although there have been studies on improving the nanostructure fabrication performance in optical nanolithography, such as on adjustable external gap spacing, additional performance enhancement is required for practical applications and commercialization of large-area and high-resolution nanostructure array fabrication techniques. In this study, we design and apply a plasmonic bull’s eye nanostructured meta-mask to enhance the performance of optical nanolithography. Through simulation results and experimental verification, it is confirmed that advanced optical nanolithography using the bull’s eye nanostructured meta-mask has several merits compared to conventional Talbot lithography using nanoholes: (1) Optical nanolithography using the bull’s eye nanostructured meta-mask effectively fabricates nanopillar arrays even at a shorter exposure time than conventional optical lithography using nanoholes. (2) It is possible to create a large-area nanopillar array with various nanopillar diameters by exposure time control in optical nanolithography using the bull’s eye meta-mask. (3) Using water or objective immersion oil to increase the refractive index of the contact medium, light can be focused on smaller sizes, and large-area nanopillar arrays with smaller nanopillar diameters are established. With the upgradation of hardware for large-area fabrication, application of immersion media supplying techniques, and additional studies to establish complex nanostructures, optical nanolithography using the bull’s eye nanostructured meta-mask is an efficient modality to produce various nanostructure-based devices.